VIth International Congress on Thrombosis and Haemostasis 1977
DOI: 10.1055/s-0039-1680501
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Surface Negative Charge in Human Platelets by Ristocetin

Abstract: The effect of ristocetin on the platelet surface charge was examined. One part of citrated PRP or platelet suspensions was mixed with nine parts of lOμM Tris-buf f ered saline (pH 7.4) and the mixtures were incubated at 25°C with or without ristocetin. These mixtures were applied for a cell electrophoresis microscope to determine the electrophoretic mobility(EM), from which the platelet surface charge was estimated. A significant reduction in surface negative charge of platelets was observed when ristocetin wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1980
1980
1999
1999

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…32 We ourselves have confirmed this result in two patients. However, Coller and Muraki et al 33 have shown that ristocetin reduced platelet charge at doses of 0.5 and 1 mg/ml, but no change was observed when normal platelets were suspended in plasma taken from a patient with Willebrands disease. According to this result, which should be confirmed and studied in further detail, it might be assumed that positively charged ristocetin is adsorbed on the platelet membrane by forming a complex with the Willebrand factor.…”
Section: Electrophoretic Mobility and Thrombopathymentioning
confidence: 98%
“…32 We ourselves have confirmed this result in two patients. However, Coller and Muraki et al 33 have shown that ristocetin reduced platelet charge at doses of 0.5 and 1 mg/ml, but no change was observed when normal platelets were suspended in plasma taken from a patient with Willebrands disease. According to this result, which should be confirmed and studied in further detail, it might be assumed that positively charged ristocetin is adsorbed on the platelet membrane by forming a complex with the Willebrand factor.…”
Section: Electrophoretic Mobility and Thrombopathymentioning
confidence: 98%